IL‐35 enhances angiogenic effects of small extracellular vesicles in breast cancer. (11th February 2022) - Liu, Jia; Dong, Nana; Li, Ning; Zhao, Hui; Li, Yali; Mao, Huihui; Ren, Hanxiao; Feng, Yimin; Liu, Jie; Du, Lutao; Mao, Haiting
Abstract : As an indispensable process for breast cancer metastasis, tumour angiogenesis requires a tight interaction between cancer cells and endothelial cells in tumour microenvironment. Here, we explored the participation of small extracellular vesicles (sEVs) derived from breast cancer cells in modulating angiogenesis and investigated the effect of IL‐35 in facilitating this process. Firstly, we characterized breast cancer cells‐derived sEVs untreated or treated with IL‐35 and visualized the internalization of these sEVs by human umbilical vein endothelial cells (HUVECs). Breast cancer cells‐derived sEVs promoted endothelial cell proliferation through facilitating cell cycle progression and enhanced capillary‐like structures formation and microvessel formation. Subsequent results proved that IL‐35 further reinforced the angiogenic effect induced by breast cancer cells‐derived sEVs. Moreover, sEVs from breast cancer cells significantly enhanced tumour growth and microvessel density in breast tumour‐bearing mice model. Microarray analysis showed that IL‐35 might alter the mRNA profiles of sEVs and activate the Ras/Raf/MEK/ERK signalling pathway. These findings demonstrated that IL‐35 indirectly promoted angiogenesis in breast cancer through regulating the content of breast cancer cells‐derived sEVs, which could be internalized by HUVECs. Abstract : Tumour angiogenesis requires a tight interaction between cancer cells and endothelial cells. Small extracellular vesicles (sEVs) are vital mediators for intercellular communication and facilitate the exchange of proteins and nucleic acids between cells. Here, we describe that IL‐35 treatment reinforces the angiogenic effect of breast cancer cells‐derived sEVs by increasing the expression of CALM1 and activating the Ras/Raf/MEK/ERK signalling pathway.